A potential novel pathological implication of serum soluble triggering receptor expressed on myeloid cell 2 in insulin resistance in a general Japanese population: The Hisayama study. (December 2018) - Tanaka, Masashi; Honda, Takanori; Yamakage, Hajime; Hata, Jun; Yoshida, Daigo; Hirakawa, Yoichiro; Shibata, Mao; Inoue, Takayuki; Kusakabe, Toru; Satoh-Asahara, Noriko; Ninomiya, Toshiharu
Highlights: Waist circumference and fat mass index increased with higher serum sTREM2 levels. Greater serum sTREM2 levels were associated with insulin resistance. sTREM2 can be a novel target to elucidate mechanisms underlying insulin resistance. Abstract: Aims: No cohort study has examined the pathological significance of triggering receptor expressed on myeloid cell 2 (TREM2), a cell surface receptor expressed on myeloid lineage cells, and its soluble form, sTREM2, in insulin resistance in a general population. Methods: A total of 2742 community-dwelling Japanese individuals aged ≥40 years were divided into 4 groups according to the serum sTREM2 concentration quartiles. We examined the cross-sectional association of sTREM2 levels with anthropometric parameters and the homeostasis model assessment of insulin resistance (HOMA-IR). Results: The median sTREM2 concentrations was 255.6 (interquartile range, 162.5–419.2) pg/mL. In multivariate analyses, waist circumference and fat mass index increased with elevating sTREM2 levels ( P for trend: <0.001 and 0.02, respectively), but there was no significant association between sTREM2 levels and body mass index and fat-free mass index. Among the subjects without taking antidiabetic medications (n = 2610), greater sTREM2 levels were associated with higher HOMA-IR ( P for trend <0.001) even after adjusting for waist circumference, fat mass index, and high-sensitivity C-reactive protein. Conclusions: Our findings suggest that serum sTREM2 had novel pathological roles in insulin resistance, while obesity and inflammation had no substantial effects on the relationship between sTREM2 and insulin resistance in this cohort.